Alice in wonderland - Carroll, Lewis; Mohammed, Wahed ([Cairo] bayt alkotob publishing, 2025)
"One summer afternoon, a curious young mouselet named Alice follows a strange white rabbit with a pocket watch down an even stranger rabbit hole. That's the beginning of a wonderful and fabumouse journey through Wonderland, a world full of unusual characters and unforgettable adventures." -- Back cover
English stories
Keywords: English fiction